Content appealing to youth and spend characteristics of electronic cigarette video advertisements. - Hoetger, Cosima; Wall, Catherine S J; Rudy, Alyssa K; Nicksic, Nicole E; Bhatt, Sohum M; Sey, Nancy Y A; Khan, Mishaal; Braxton, Destini; Barnes, Andrew J; Cobb, Caroline O (Journal of Public Health, 2022)
Background The US electronic cigarette (ECIG) market and use behavior continues to rise, warranting investigation of ECIG advertisement (ad) content within media channels frequented by youth including internet and television (TV). In order to inform potential policy regulations, this content analysis sought to assess the prevalence of youth-appealing content and spend characteristics among ECIG video ads. Methods Between 2015 and 2016, 46 ECIG video ads were identified using an ad-tracking firm and were coded using the Content Appealing to Youth (CAY) index. Bivariate analyses and analysis of variance were used to compare CAY indices between online and TV ads and by ECIG brands. Ad-specific spend and source information, including website/TV program targeted were examined descriptively. Results Common youth-appealing features included use of animation (56.5%) and content related to positive sensations (52.2%), promoting mood (34.8%), individuality/freedom (23.9%) and addiction (19.6%). Features not associated with youth appeal also were prevalent. Few differences were observed by media source or ECIG brand. TV ads accounted for the largest spend, and Vuse was the top spending brand. Websites/TV programs were diverse. Conclusions Findings support regulatory efforts to restrict the use of youth-appealing content within ECIG ads as well as the reduction of media sources available for ECIG marketing.